Tensile Failure Mechanism of Antiseepage System for Slope with Solid Waste Underground Landfill - Liu Fei; Zhongxi Jiang (Advances in Civil Engineering)
The antiseepage membrane applied to the slope of solid waste landfill often shows tensile failure in projects, which results in ineffective antiseepage system and serious environmental pollution. In order to ensure the practical performance of the antiseepage membrane, the tensile force of it was studied, and the settlement mechanical model of the interaction between landfill body, antiseepage membrane, and cushion was established after comprehensively considering the effects of dead weight, lateral pressure, settlement, and foundation boundary. The analytical solutions of the tensile force and displacement of the antiseepage membrane was calculated through differential equation of equilibrium. With general slag and ardealite slag as the research objects, the major parameters affecting the internal tensile force of the antiseepage membrane were analyzed and studied by the combination of numerical and theoretical methods. The results show that the internal tensile force of the antiseepage membrane is greatly affected by the parameters such as the membrane-slag interface friction angle, the membrane-cushion interface friction angle, the buried depth, and the single step height. The theoretical slope normal stress and membrane pull-up force are basically consistent with the numerical calculation results, which indicates that the theory is universally applicable to tackle the tensile failure of the antiseepage membrane in the solid waste landfill system.